Disrupted Cerebellar Connectivity With the Central Executive Network and the Default-Mode Network in Unmedicated Bipolar II Disorder - Luo, Xiaomei; Chen, Guanmao; Jia, Yanbin; Gong, JiaYing; Qiu, Shaojuan; Zhong, Shuming; Zhao, Lianping; Chen, Feng; Lai, Shunkai; Qi, Zhangzhang; Huang, Li; Wang, Ying (Frontiers in Psychiatry, 2018)
Objective: Bipolar disorder (BD) is a common psychiatric disease. Although structural and functional abnormalities of the cerebellum in BD patients have been reported by recent neuroimaging studies, the cerebellar-cerebral functional connectivity (FC) has not yet been examined. The present study aims to investigate the FC between the cerebellum and cerebrum, particularly the central executive network (CEN) and the default-mode network (DMN) in BD II. Methods: Ninety-four patients with unmedicated BD II depression and 100 healthy controls (HCs) underwent the resting-state functional magnetic resonance imaging. Seed-based connectivity analyses were performed using cerebellar seeds previously identified as being involved in the CEN (bilateral Crus Ia) and DMN (bilateral Crus Ib). Results: Compared with HCs, BD II depression patients appeared decreased FC in the right Crus Ia-left dorsal lateral prefrontal cortex (dlPFC) and -left anterior cingulated cortex (ACC), the right Crus Ib-left medial prefrontal cortex (mPFC), -left middle temporal gyrus (MTG), and -left inferior temporal gyrus(ITG). No altered FC between the left Crus Ia or Crus Ib and the cerebral regions was found. Conclusions: Patients with BD II depression showed disrupted FC between cerebellum and the CEN (mainly in the left dlPFC and ACC) and DMN (mainly in the left mPFC and temporal lobe), suggesting the significant role of the cerebellum-CEN and DMN connectivity in the pathogenesis of BD.